Fonti visive di Gustave Moreau fra ricezione critica e rielaborazione poetica. Alcune note su Vittore Carpaccio e la pittura veneta - Davide Lacagnina (Annali Online dell'Università di Ferrara. Sezione Lettere)
The article reconsiders the critical and visual reception of Vittore Carpaccio in France throughout the XIX century, with a special focus on Gustave Moreau's œuvre. The months the French painter spent in Venice, his interest in Venetian painting, the sketches and the copies he made d'après, may be read in the light of a specific pursuit: define a new canon for history painting within the Academic tradition and find a personal way to most radical issues in art. Moreau's attempts to reform le grand art move from the exploration of visual and written sources of any epoch, from Antiquity to Renaissance Art, in order to find and fix ideals of highest poetical imagination, far from any popularization of history, art or literature. Among the old masters studied in Italy, Carpaccio is the most valued: the large scale compositions, the attention to detail in the decoration of interiors or in the vestments of the characters depicted, the religious sensibility of the Storie di Sant'Orsola or the frescos in the Scuola di San Giorgio degli Schiavoni are all elements inherited and elaborated by Moreau. They are not just "frozen" references taken from the past, as former scholars of Moreau mostly believed, but rather instances selected to express a peculiar vision of art, up to the definition of a symbolist theory of modern painting (poésie pure). In this sense, the literary discovery of Carpaccio in French authors such as Théophile Gautier or the brothers Edmond and Jules de Goncourt, besides the more "official" art histories of Blanc, Coindet, Rio, encompasses the moral tension arising in the taste for Italian Primitives at the end of XIX century.